Our Unruly Signs, and How We Cope with Them - Merrell, Floyd (Opción, 1970)
This paper suggests some premises that should inhere in any viable account of what C. S. Peirce called a ”˜logic of vagueness”™, a ”˜logic”™ in the ”˜broadest possible sense”™. These premises revolve around complementary interrelations between overdetermination and underdetermination, vagueness and generality, and inconsistency and incompleteness, the combination of them bearing a threat to the classical principles of Identity, Non-Contradiction, and Excluded-Middle. However, fortunately for us, it is through our detouring around these classical principles that we are able to cope with our everyday apparently unruly, illogical signs.